A Removable elevated-hinge wave generator for testing marine energy devices (Proceedings of the European Wave and Tidal Energy Conference, 2023)
A new removable elevated-hinge wave generator has been designed and commissioned in the O.H. Hinsdale Wave Research Laboratory (HWRL), at Oregon State University. The wave maker, built by Edinburgh Designs Ltd., is comprised by six electrically actuated dry-back paddles, self-contained in a single steel box and capable of generating mid-scale regular, irregular and user defined waves in a typical range of periods from 0.5 to 4 s at a maximum depth of 4 m. The system is intended to increase the available depth range in the Large Wave Flume (LWF) and satisfy the demand of intermediate to deep water waves at a relatively large scale by the marine energy industry.The existing Large Wave Flume at the HWRL, is currently equipped with a piston-type, dry-back wave generator with a 4.2 m maximum stroke hydraulic actuator assembly. The flume is 104.24 m long, 3.66 m wide, and the sidewalls are 4.57 m high. The existing wave maker can generate large regular, random and tsunami-like long waves for the purpose of large-scale model tests, particularly in the area of coastal hazards (storm waves and tsunamis). Currently, the maximum water depth for generation of regular or random waves is 2.7 m, with a maximum wave height of 1.7 m in a wave period range from 4 to 8 s. The maximum depth for tsunami-like waves (solitary waves) in the flume is 2.0 m, with a maximum wave height of 1.4 m. The LWF works as a standard coastal (shallow water) testing facility where the models, bathymetry and instrumentation are typically installed with the facility completely empty. This allows for a full range of testing depths (from practically 0 to the maximum depth corresponding to the wave type to be generated). Correct representation of the bathymetry is necessary in coastal studies since wave propagation, transformation and breaking is part of the intended research. However, intermediate to deep water conditions, required for medium scale marine energy studies, represented a challenge.The maximum depth at the flume for wave generation was limited by the structural design of the wave machine. However, the flume wall height is capable of handling a maximum depth in excess of 4 m. To increase the capabilities of the facility and responding to an increasing demand of deeper experimental conditions (particularly from the wave energy industry), the procurement of a specialized wave machine able to generate high-quality waves in deeper water was deemed necessary.The uniqueness of the system relies on its flexibility. It was conceived to be, first, removable and can be relocated anywhere along the flume, at the full range of depths (from 1 m to 4 m) and it can be reversed facing both directions along the flume. This flexibility, required by the intention to keep the existing wave machine operational, increases its functionality by making it compatible to the generation of waves and co-linear currents, as well as expanding the available testing section along the flume, with generation on one side and absorption on the opposite.